Energy management system of microgrid: Control schemes, pricing techniques, and future horizons. (6th April 2021) - Touma, Haider Jouma; Mansor, Muhamad; Rahman, Muhamad Safwan Abd; Kumaran, Vigna; Mokhlis, Hazlie Bin; Ying, Yong Jia; Hannan, M. A.
Summary: The tremendous engagement of electric energy consumers and the advent of smart grids have left more complexity and challenges in terms of energy management system. Recently, microgrid is a preferable choice to cope with these challenges as small‐scale power system and so close to consumers. However, there is a crucial need to find more compatible solutions to achieve economic, environmental, and reliable objectives of energy management system, since most current solutions are based on optimal scheduling of generating units at the supply side. Demand side management develops more opportunities to achieve these objectives by efficiency programs and demand response programs (pricing techniques). Therefore, this article reviews and assesses demand side management, particularly pricing techniques, in the light of energy management system as a part of control system of microgrid. Furthermore, the aspects of control schemes are discussed including centralized and distributed controls. Finally, this article identifies a number of shortcomings in the current research that concern demand side management and highlights future horizons of research.